2019
DOI: 10.3389/fevo.2019.00031
|View full text |Cite
|
Sign up to set email alerts
|

Variation From an Unknown Source: Large Inter-individual Differences in Migrating Black-Tailed Godwits

Abstract: Variation in migratory behavior is the result of different individual strategies and fluctuations in individual performances. A first step toward understanding these differences in migratory behavior among individuals is, therefore, to assess the relative contributions of inter-and intra-individual differences to this variation. We did this using light-level geolocators deployed on the breeding grounds to follow continental black-tailed godwits (Limosa limosa limosa) throughout their south-and northward migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
67
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 59 publications
2
67
1
Order By: Relevance
“…We speculate that the generally larger, intra-individual variation (up to 24 days) that we found for martins as compared to other songbirds (Stanley et al, 2012;Both et al, 2016;Pedersen et al, 2018), may reflect the nature of migration and social behavior in martins, and possibly other swallows. The intraindividual variability we found for purple martins is more similar to broad, within-individual variation recently shown for some shorebirds (Senner et al, 2019;Verhoeven et al, 2019), than to data reported for nocturnally migrating songbirds. Purple martins are diurnal migrants that roost in large flocks during stopovers across migration (Brown and Tarof, 2013), and may use island-like habitats for stopover (Fraser et al, 2017;Fournier et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…We speculate that the generally larger, intra-individual variation (up to 24 days) that we found for martins as compared to other songbirds (Stanley et al, 2012;Both et al, 2016;Pedersen et al, 2018), may reflect the nature of migration and social behavior in martins, and possibly other swallows. The intraindividual variability we found for purple martins is more similar to broad, within-individual variation recently shown for some shorebirds (Senner et al, 2019;Verhoeven et al, 2019), than to data reported for nocturnally migrating songbirds. Purple martins are diurnal migrants that roost in large flocks during stopovers across migration (Brown and Tarof, 2013), and may use island-like habitats for stopover (Fraser et al, 2017;Fournier et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…The random intercepts were clutch, individual, year and polder. Individual Godwits consistently winter either north or south of the Sahara (Verhoeven et al 2019). To determine whether this consistent migratory behaviour results in consistent differences in egg size, we corre-lated egg size with wintering location.…”
Section: Discussionmentioning
confidence: 99%
“…Although the strength of the trade winds over the Sahara varies between years (Taylor et al ), trans‐Saharan migrants seemingly have evolved a diverse suite of strategies to cope with the synoptic phenomena that determine local wind patterns in the region (Kranstauber et al ; Evan et al ; Vansteelant et al ). In the case of godwits, previous studies have shown that they can exhibit flexibility in the timing of their Sahara crossings (Verhoeven et al ), dynamically adjust their flight altitude in response to temperature and wind conditions (Senner et al ), and have the ability to use emergency stopover sites at the beginning of their southward Sahara crossing (after ~ 500 km) or during the final part of their northward Sahara crossing (after ~ 2000 km). Nevertheless, despite these presumed adaptive behaviours, our results indicate that these are not sufficient to ensure safe crossings of the Sahara, at least not during northward crossings.…”
Section: Discussionmentioning
confidence: 99%
“…Future work should embrace this new frontier and aim to understand how migrants assess departure and en route conditions, and why 6 h of extra flight can be a cause of death in birds that can prepare for over 200 h of non‐stop flight (Gill et al ). Part of the answer may have to do with learning, making it likely that migratory behaviours, including the decision to initiate migration, may change over the course of an individual’s life (Sergio et al ; Verhoeven et al ).…”
Section: Discussionmentioning
confidence: 99%